Zmiany w polskiej agencji promującej inwestycje w kontekście utworzenia Polskiej Agencji Handlu i Inwestycji - Kuźmińska, Aleksandra (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The importance of foreign direct investment (FDI) for economic development increases attention for attraction of FDI and establishment of the investment promotion programmes. Those programmes are usually conducted by investment promotion agencies (IPA). Although the investment promotion agency has been set up in Poland (Polish Information and Foreign Investment Agency), it is far from the patterns established by its effective counterparts. This article presents forthcoming changes in the Polish IPA. The new agency - Polish Trade and Investment Agency - will have much wider competencies than the former one. It will be responsible for overall economic promotion, it will join investment and export promotion. In the area of investment promotion it will be able to target investors and will present a complex investment offer, it will work as one-stop-shop. The project of the new agency looks promising, however, we will only be able to assess the effects once the legal act has come into force and the agency has been established. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (16); 2008; nr 1193, s. 170-178